DETERMINAN INISIASI MENYUSUI DINI PADA WANITA USIA SUBUR DI PROVINSI SUMATRA UTARA (Analisis Data SDKI 2017) - Fajriyah, Endah Nur; Rosidati, Catur (Faculty of Health Sciences, Syarif Hidayatullah State Islamic University of Jakarta, 2021)
Early initiation of breastfeeding (EIBF) is the process of placing the baby on the mother's chest or stomach immediately after birth to make it easier for the baby to initiate the breastfeeding process which lasts for at least one hour. EIBF is highly recommended in addition to preventing the cause of death in infants as well as supporting the success of the exclusive breastfeeding program and allowing babies to get colostrum. Based on the Indonesian Demographic and Health Survey in 2017, the implementation of EIBF in Indonesia is relatively low, namely 57%. North Sumatra is the province with the lowest EIBF coverage in Indonesia, namely 24.2%. This coverage is still far from the target of the Ministry of Health’s Strategic Plan which targets the percentage of newborns receiving EIBF of 50%. The purpose of this study was to determine the factors that most influence the early initiation of breastfeeding in North Sumatra. The research design used was a cross-sectional design. This study used secondary data that was the Indonesian Demographic and Health Survey data in 2017. The data analysis used was a multivariate logistic regression with determinant factors. The number of samples in this study was 669 mothers who had given birth with the last birth occurred in the five years before the survey. The results showed three variables were determinants of early initiation of breastfeeding. The most dominant factor affecting early breastfeeding was the type of childbirth variable with an odds ratio of 5.060 (95% CI 2.714-9.435), it’s means respondents who had caesarean section were 5 times more likely to not EIBF as compared to respondents who had vaginal delivery. Therefore, it is recommended health workers provide counseling to mothers about the importance of EIBF. Additionally, health workers who assist in the childbirth process are expected to provide opportunities for mothers to carry out EIBF and help mothers so that the EIBF process runs well.Keyword: Early initiation of breastfeeding, women of childbearing age, and determinants factorAbstrakInisiasi menyusui dini (IMD) merupakan proses meletakkan bayi di dada atau perut ibu segera setelah lahir untuk memudahkan bayi dalam memulai proses menyusui yang berlangsung selama sedikitnya satu jam. IMD sangat dianjurkan selain untuk mencegah penyebab kematian pada bayi juga sebagai pendukung keberhasilan program ASI eksklusif serta memberi kesempatan kepada bayi untuk mendapatkan kolostrum. Berdasarkan Survei Demografi dan Kesehatan Indonesia tahun 2017 pelaksanaan IMD di Indonesia relatif rendah, yaitu 57%. Sumatera Utara merupakan provinsi dengan cakupan IMD terendah di Indonesia, yaitu 24,2%. Cakupan tersebut masih jauh dari target Renstra Kemenkes yang menargetkan persentase bayi mendapat IMD sebesar 50%. Tujuan dari penelitian ini adalah untuk mengetahui faktor yang paling berpengaruh terhadap inisiasi menyusui dini di Sumatera Utara. Desain penelitian yang digunakan adalah cross sectional. Penelitian ini menggunakan data sekunder, yaitu data Survei Demografi dan Kesehatan Indonesia tahun 2017. Analisis data yang digunakan adalah multivariat regresi logistik faktor determinan. Jumlah sampel pada penelitian ini sebanyak 669 ibu yang pernah melahirkan dengan persalinan terakhir terjadi dalam lima tahun sebelum survei. Hasil penelitian menunjukkan bahwa terdapat tiga variabel yang menjadi determinan terhadap inisiasi menyusui dini. Adapun faktor yang paling dominan memengaruhi inisiasi menyusui dini adalah variabel jenis persalinan dengan nilai odds ratio sebesar 5,060 (95%CI 2,714-9,435), yang artinya responden yang melahirkan dengan operasi sesar berpeluang 5 kali lebih besar untuk tidak IMD dibandingkan dengan responden yang melahirkan secara normal. Oleh karena itu, disarankan kepada tenaga kesehatan agar memberikan konseling kepada ibu mengenai pentingnya IMD. Selain itu, bagi tenaga kesehatan yang membantu proses persalinan diharapkan dapat memberikan kesempatan kepada ibu untuk melakukan IMD serta membantu ibu agar proses IMD berjalan dengan baik.Kata Kunci: Inisiasi menyusui dini, wanita usia subur, dan faktor determinan